The aims of employability and social inclusion / active citizenship in lifelong learning policies in Greece - Prokou, Eleni (The Greek Review of Social Research, 2011)
The argument of this article is that during the last two decades or so, in lifelong learning policies in Greece, priority was given to the confrontation of social exclusion that stems from unemployment and, thus, to the achievement of the aims of employability and social inclusion. EU funding and the relatively centralised character of the regulated part of adult/continuing education in Greece favoured the expansion of training programmes for the unemployed. As in the 1990s, so in the 2000s, the Greek State supported continuing vocational training which, however, was widely privatised. Thus, privatisation and the absence of coherent measures that would link education with employment, posed questions as to the fulfilment of the mission of fighting unemployment and consequently, social exclusion. At the same time, the fact that policies gave less importance to general adult education, posed challenges for adult education in Greece to meet all of its aims, which apart from employability include realisable social inclusion, active citizenship and personal development.